2011
DOI: 10.1371/journal.pone.0027231
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptome and Binding Sites Analysis Implicates E2F in the Regulation of Self-Renewal in Human Pluripotent Stem Cells

Abstract: Rapid cellular growth and multiplication, limited replicative senescence, calibrated sensitivity to apoptosis, and a capacity to differentiate into almost any cell type are major properties that underline the self-renewal capabilities of human pluripotent stem cells (hPSCs). We developed an integrated bioinformatics pipeline to understand the gene regulation and functions involved in maintaining such self-renewal properties of hPSCs compared to matched fibroblasts. An initial genome-wide screening of transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 58 publications
(82 reference statements)
0
25
0
Order By: Relevance
“…In line with the promoter analysis, E2F1 expression and its target genes were found to be downregulated upon ENPP1 knockdown. Although a stem cell relevant role of E2F1 was so far not investigated in GSCs, E2F1 was shown to be of particular importance in the maintenance of neural stem cells 41 and human pluripotent stem cells 42 as well as in a transcriptional regulatory network governing the maintenance of embryonic stem cells. 43 Given the central role of E2F1 in the regulation of cell cycle progression, it is reasonable to assume that the observed reduced proliferation and accumulation of cells in G1 cell cycle phase in E-NPP1-deficient GSCs is mediated by a decreased transcriptional function of E2F1.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the promoter analysis, E2F1 expression and its target genes were found to be downregulated upon ENPP1 knockdown. Although a stem cell relevant role of E2F1 was so far not investigated in GSCs, E2F1 was shown to be of particular importance in the maintenance of neural stem cells 41 and human pluripotent stem cells 42 as well as in a transcriptional regulatory network governing the maintenance of embryonic stem cells. 43 Given the central role of E2F1 in the regulation of cell cycle progression, it is reasonable to assume that the observed reduced proliferation and accumulation of cells in G1 cell cycle phase in E-NPP1-deficient GSCs is mediated by a decreased transcriptional function of E2F1.…”
Section: Discussionmentioning
confidence: 99%
“…An important clue to understanding the plethora of E2F functions came from integrated bioinformatics (6). The authors identified generation of energy, protein transport and metabolism as non-canonical ontology categories for genes with E2F binding sites.…”
Section: E2f Regulates Mitochondrial Function In Drosophilamentioning
confidence: 99%
“…Recent studies revealed that E2F/DP influences efficiency of apoptosis via regulation of nuclear-encoded mitochondria-associated genes (11). Bioinformatics approach uncovered multiple new roles of E2Fs (shown in yellow area) (6,7). Accumulating evidence suggests that E2F regulates genes involved in mitochondrial functions through direct binding to their promoter regions (left) and through interactions with the NRF1, NRF2, HCF1 and PPAR, key regulatory factors of mitochondrial biogenesis (right).…”
Section: Figurementioning
confidence: 99%
“…This repression of Cdk inhibitors is E2F4-dependent, a reflection of the complex transcriptional role of the E2Fs, where E2F4–6 are transcriptional inhibitors rather than transcriptional activators and S-phase inducers [18,40]. Not surprisingly, activating E2Fs are implicated in the regulation of many pathways in ES cells, including the core pluripotency network genes Oct4 , Sox2 , and Nanog , as well as the Wnt and FGF pathways [39,41]. On the other hand, knockdown of E2F2 alone, reduced the proliferation of ES cells, but pluripotency was not effected [42].…”
Section: Reciprocal Regulation Of Cell Cycle and Pluripotency Networkmentioning
confidence: 99%